2022
DOI: 10.3389/fphar.2022.1011624
|View full text |Cite
|
Sign up to set email alerts
|

Insulin degludec/liraglutide versus its monotherapy on T2D patients: A lifetime cost-utility analysis in China

Abstract: Introduction: IDegLira (brand name Xultophy) is a novel fixed ratio combination of insulin degludec and liraglutide for type 2 diabetes (T2D) patients. This study aimed to investigate the lifetime cost-effective value of IDegLira compared with its single component (Degludec or Liraglutide) and to explore the suitable annual cost of IDegLira if necessary.Methods: UKPDS OM2 was applied to determine the long-term quality-adjusted life years (QALYs) and total costs. The efficacy data that were inputted into the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…IDegLira was first listed in Switzerland in 2015. 27 In 2017, the -9 of 12 (48 mmol/mol) was significantly higher than that of insulin or GLP-1RA, respectively. The above results showed that IDegLira had better advantages in blood glucose control and is recommended for reducing blood sugar in T2DM in terms of efficacy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…IDegLira was first listed in Switzerland in 2015. 27 In 2017, the -9 of 12 (48 mmol/mol) was significantly higher than that of insulin or GLP-1RA, respectively. The above results showed that IDegLira had better advantages in blood glucose control and is recommended for reducing blood sugar in T2DM in terms of efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…IDegLira was first listed in Switzerland in 2015 27 . In 2017, the Food and Drug Administration (FDA) approved IDegLira to be listed in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…A combination therapy of IDegLira did not demonstrate 'financial superiority' over its monotherapy components (IDeg and Lira) in the treatment of T2D in a CUA conducted in China [34]. No gains were observed in QALYs (11.79, 11.62, and 11.73, respectively), medications costs (USD 20,281.61, USD 3726.76 and USD 11,941.26, respectively), complication costs (USD 25,274.22, USD 25,016.67 and USD 25,204.84, respectively), total costs (USD 45,555.83, USD 28,743.43 and USD 36,660.18, respectively), incremental cost-utility ratio values (USD 99,464.12/QALYs and USD 143,348.26/QALYs, respectively; both surpassed the WTP threshold) nor net monetary benefits (−10,447.67 and −6200.68, respectively).…”
Section: Cua Studiesmentioning
confidence: 83%
“…The latter of these is significant, as all of the studies reporting IDeg and similar insulin mixes to be more effective than insulin glargine variants considered hypoglycemic events, which were key in determining IDeg variants to be more cost-effective. Additionally, a CUA in China found treatment with combination therapy iDegLira to be significantly less cost-effective than either degludec or liraglutide monotherapy despite achieving the highest QALY, due to its high cost in the Chinese market [34].…”
Section: Discussionmentioning
confidence: 99%